2000
DOI: 10.1152/ajpendo.2000.278.5.e759
|View full text |Cite
|
Sign up to set email alerts
|

Role of C-peptide in human physiology

Abstract: The C-peptide of proinsulin is important for the biosynthesis of insulin but has for a long time been considered to be biologically inert. Data now indicate that C-peptide in the nanomolar concentration range binds specifically to cell surfaces, probably to a G protein-coupled surface receptor, with subsequent activation of Ca(2+)-dependent intracellular signaling pathways. The association rate constant, K(ass), for C-peptide binding to endothelial cells, renal tubular cells, and fibroblasts is approximately 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
212
3
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(230 citation statements)
references
References 52 publications
6
212
3
9
Order By: Relevance
“…Firstly, C-peptide effects could result from direct binding to, and activation of, a specific C-peptide receptor. Although the presence of such a receptor has not been unequivocally proven, a putative receptor has been found [2,8]. Investigations suggest that the C-peptide receptor is a surface entity probably coupled to its signal transduction pathway by a G protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, C-peptide effects could result from direct binding to, and activation of, a specific C-peptide receptor. Although the presence of such a receptor has not been unequivocally proven, a putative receptor has been found [2,8]. Investigations suggest that the C-peptide receptor is a surface entity probably coupled to its signal transduction pathway by a G protein.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment of cells with pertussis toxin abolishes specific C-peptide binding [8]. This observation, along with inhibition of several C-peptide effects by pertussis toxin, indicates that C-peptide binds to a G-protein coupled receptor [2,8]. Human C-peptide stimulates glucose transport in human non-diabetic and diabetic skeletal muscle [9,10].…”
mentioning
confidence: 87%
“…It connects the A and B chains of insulin in the precursor molecule proinsulin, which is stored in secretory granules of the pancreatic b-cell (1-3). C-peptide facilitates the formation of the correct secondary and tertiary structure of the hormone during insulin biosynthesis (3,4). C-peptide and insulin are secreted in equimolar amounts; however, C-peptide does not undergo significant hepatic metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma C-peptide levels are often used as a marker of actual insulin secretion, and inversely related to the development of diabetic complications including neuropathy [22,28,29]. For a long time, C-peptide had been considered to be biological inert.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, C-peptide had been considered to be biological inert. However, recent studies have shown that C-peptide is an active peptide hormone with potentially important physiological effects against diabetic complications in patients with type 1 diabetes and experimental models [2,4,8,10,11,22,28,29]. For example, short-term infusion of C-peptide improves impaired cardiac autonomic nerve functions, mainly parasympathetic components, in patients with polyneuropathy and type 1 diabetes [10].…”
Section: Introductionmentioning
confidence: 99%